Fiscal composition and long-term growth - António Afonso; Jo\~ao Tovar Jalles (European Central Bank (ECB), 2013)
We assess the fiscal composition-growth nexus, using a large country panel, accounting for the usually encountered econometric pitfalls. Our results show that revenues have no significant impact on growth whereas expenditures have negative effects. The same is true for the OECD with the addition that government revenue has a negative impact on growth. From our results, taxes on income are not growth enhancing, as well as public wages, interest payments, subsidies and government consumption. Spending on education and health boosts growth; and there is weak evidence supporting causality running from expenditures and revenues to output.
Keywords: C23; E62; H50; 330; budget decomposition; budget deficit; panel analysis; panel causality